2021
DOI: 10.20448/journal.509.2021.82.135.142
|View full text |Cite
|
Sign up to set email alerts
|

Strategy to Improve English Vocabulary Achievement during Covid-19 Epidemic. Does Quizizz Help?

Abstract: Science, Technology, Engineering, and Mathematics (STEM) education is being increasingly recognized as needing vital emphasis at a national level. To enhance learning in Science and Mathematics, the repertoire of vocabularies plays a significant role. As the coronavirus disease 2019 (COVID-19) continues its spread across the world, people's vocabulary learning has been limited. Responding to this situation with appropriate awareness, e-learning is being applied to teach the English language. The intent of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 31 publications
3
6
0
2
Order By: Relevance
“…These results demonstrated that Quizizz application significantly improved students' vocabulary mastery compared to other similar apps used in the control group. Positive feedback and attitudes from students towards Quizizz as a learning medium were also observed in this study, in line with previous research findings (Huei et al, 2021;Irwansyah & Izzati, 2021). These findings suggest that Quizizz can be effective tools for improving students' vocabulary mastery in English.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results demonstrated that Quizizz application significantly improved students' vocabulary mastery compared to other similar apps used in the control group. Positive feedback and attitudes from students towards Quizizz as a learning medium were also observed in this study, in line with previous research findings (Huei et al, 2021;Irwansyah & Izzati, 2021). These findings suggest that Quizizz can be effective tools for improving students' vocabulary mastery in English.…”
Section: Discussionsupporting
confidence: 92%
“…To this end, researchers have explored the use of Quizizz and other similar applications as learning media to improve vocabulary mastery among students. Several similar studies have reported that Quizizz and other similar applications are effective in enhancing students' vocabulary mastery (Arttırmak & Samet, 2018;Huei et al, 2021;Nguyen, 2022). In a similar vein, a recent study implemented Quizizz and other similar applications as learning media to address vocabulary mastery issues (Alhebshi & Gamlo, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…Because through this media, students compete with their friends to increase their learning motivation (Zulfa & Ratri, 2022). With Quizizz also, the scores displayed on the leaderboard can provide a positive learning experience (Mohamad et al, 2020;Huei et al, 2021). Furthermore, in the 6th (sixth) statement, 95% of students agreed that the Quizizz media taught them to appreciate the time allotted to work on the questions.…”
Section: Discussionmentioning
confidence: 99%
“…This is reiterated by Mansur and Fadhilawati (2019) in their study where the use of Kahoot application was able to improve students' English Vocabulary achievement that eventually increased their vocabulary learning result from 59.23 to 84.58. Similarly, Huei et al (2021) performs research on Quizizz in improving vocabulary achievement among primary English as Secondary Language (ESL) pupils in rural schools. The finding revealed that Quizizz was able to arouse a positive learning environment and provides an engaging learning environment by recapping words which helps the pupils to enhance their vocabulary learning.…”
Section: Motivation In Learningmentioning
confidence: 99%